Women’s Objectification in Ighāshat Mīlā by Fatimah Sharafeddine: A Feminist Analytical Study - Sari, Novita (Litteratura: Jurnal Bahasa dan Sastra, 2025)
This study aims to reveal the forms of objectification experienced by the character Mila in the novel Ighāshat Mīlā by Fatimah Sharafeddine. The research employs a descriptive qualitative method with close-reading techniques, examining events, dialogues, and character actions. This study is grounded in a feminist literary approach and applies Martha Craven Nussbaum’s theory of objectification. The findings indicate that Mila experiences four forms of objectification: the denial of women’s autonomy (denial of autonomy), treating women as objects that can be harmed without regard to their feelings (violability), the negation of women’s subjectivity (denial of subjectivity), and the perception that women lack the capacity to act or move independently, akin to inanimate objects (inertness). From this analysis, it can be concluded that women in Lebanon continue to strive for equal access and rights with men, as well as for liberation from male dominance and oppression across various spheres of life.